Adverse effects of proton-pump inhibitor use in older adults: a review of the evidence. (September 2017) - Maes, Marina L.; Fixen, Danielle R.; Linnebur, Sunny Anne
Proton-pump inhibitors (PPIs) are a widely prescribed class of medications used to treat acid-related disorders and use has significantly increased over the last few decades. PPIs are often inappropriately prescribed and since they have been on the market, a number of post-marketing studies have been published demonstrating associations between longer duration of PPI therapy and a number of adverse effects that are a concern in older adults. The objective of this review is to discuss the existing literature of potential adverse effects with long-term PPI use in older adults and to summarize the implications in clinical practice. A PubMed search was conducted to identify studies evaluating the potential long-term adverse effects of PPI therapy in older adults, and publications were selected based on relevant criteria. PPIs have been associated with an increased risk of a number of adverse effects including osteoporotic-related fractures, Clostridium difficile infection, community-acquired pneumonia, vitamin B12 deficiency, kidney disease, and dementia, demonstrated by a number of case-control, cohort studies, and meta-analyses. Older adults should be periodically evaluated for the need for continued use of PPI therapy given the number of potential adverse effects associated with long-term use.